2013
DOI: 10.1186/1750-1172-8-42
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II clinical trial of enzyme replacement therapy with idursulfase beta in patients with mucopolysaccharidosis II (Hunter Syndrome)

Abstract: BackgroundMucopolysaccharidosis II (MPS II, Hunter syndrome) is a rare X-linked lysosomal storage disorder caused by the deficiency of iduronate-2-sulfatase (IDS). In affected patients, glycosaminoglycan (GAG) accumulates in the lysosomes of many organs and tissues contributing to the pathology associated with MPS II. The objective of this phase I/II clinical study was to evaluate the efficacy and safety of recombinant human iduronate-2-sulfatase (idursulfase beta, Hunterase®) in the treatment of MPS II.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
1
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 14 publications
1
60
1
9
Order By: Relevance
“…A 24-week randomized, single-blinded, active comparator-controlled, phase I/II clinical trial of idursulfase beta was conducted to evaluate its efficacy and safety in the treatment of MPS type II patients. This study (31) was the first active comparator-controlled clinical trial of idursulfase beta for Korean male patients with MPS type II. The idursulfase beta treatment was well tolerated by Korean patients with MPS type II and resulted in a significant reduction in urinary GAG excretion as well as an improvement in the distance on the six-minute walking test when compared to the active comparator.…”
Section: Development Of Idursulfase Beta and Phase I/ii Clinical Triamentioning
confidence: 99%
“…A 24-week randomized, single-blinded, active comparator-controlled, phase I/II clinical trial of idursulfase beta was conducted to evaluate its efficacy and safety in the treatment of MPS type II patients. This study (31) was the first active comparator-controlled clinical trial of idursulfase beta for Korean male patients with MPS type II. The idursulfase beta treatment was well tolerated by Korean patients with MPS type II and resulted in a significant reduction in urinary GAG excretion as well as an improvement in the distance on the six-minute walking test when compared to the active comparator.…”
Section: Development Of Idursulfase Beta and Phase I/ii Clinical Triamentioning
confidence: 99%
“…The common clinical presentations are a large head (dolicocephalic), short stature, mental retardation, coarse facial features, a proturbent abdomen, a broad nose with flared nostril, large tongue and musculoskeletal deformities. Other features include upper respiratory infections, valvular heart diseases, enlarged liver and spleen, umbilical as well as inguinal hernia, skin lesions, hypoplastic enamel and carious teeth [1,3,4,6,7,8]. Most of the signs were present in our case.…”
Section: Discussionmentioning
confidence: 66%
“…Diagnosis is usually made in the second decade of life. Death usually occurs in the fourth decade and the main cause of death is cardiac failure [3,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 A second recombinant enzyme, idursulfase beta (Hunterase ® , Green Cross Corp, Yongin, Korea), has been produced from the Chinese hamster ovary cell line by genetic engineering yielding a glycosylated protein analogous to the native human enzyme. 16,17 Its safety and a similar efficacy compared to idursulfase had been demonstrated by a successful clinical trial 16 in Korean patients with MPS II older than 6 years, leading to the recent approval of idursulfase beta by the Korean Ministry of Food and Drug Safety. A second clinical trial demonstrated that the safety and efficacy profile of 0.5 mg/kg/week of idursulfase beta infusion in patients younger than 6 years was similar to that previously reported for older Hunter syndrome patients.…”
mentioning
confidence: 99%